Equity and Amerindians in Montaigne’s “Des cannibales” (1, 31) - Connolly, Shannon R. (Renaissance and Reformation / Renaissance et Réforme, 2020)
Since the first publication of the Essais in Bordeaux in 1580, readers of this work have recognized skepticism underlying the judgment of its author, Michel de Montaigne. Arguing that the Pyrrhonist school of skepticism relies upon cultural diversity, or that Montaigne was influenced by sixteenth-century proto-ethnographic accounts of European travellers to the New World, many scholars of the Essais have read “Des cannibales” (1, 31) as proto-anthropological. In my close reading of this chapter, however, I contend that Montaigne’s rhetorical use of equity, and not his debated practice of a proto-anthropological cultural relativism, shares a special reciprocity with his skeptical judgment in the Essais. Equity, a para-legal procedure that Montaigne used to judge while he was a magistrate in the Bordeaux parlement (1557–70), remains largely underdeveloped in scholarship on the Essais.